Generation of MiRNA sponge constructs targeting multiple MiRNAs. Issue 7 (6th June 2022) - Jie, Junjin; Liu, Danni; Wang, Yifan; Wu, Qiong; Wu, Tingting; Fang, Rong
Abstract: Background: MicroRNAs(miRNAs) are key regulators of gene expression in plants, animals and some viruses. Hence, alteration of miRNA levels in cells or tissues is common for miRNA studies. Loss‐of‐function of miRNA can be achieved using antisense oligonucleotides, sponges and gene knockout models. Methods: Here, we showed an efficient, rational and economical way to construct multi‐targeted miRNA sponges with desired copies. Four copies of miRNA sponge are used as "building‐blocks". Results: These building‐blocks, which can target same miRNA or different miRNAs, are linked together through ligation. Each time of ligation can double the number of sponge copies. Conclusions: In this way, we constructed lentivirus vectors harboring sponges targeting miR‐21, miR‐31 and miR‐155 and the combination of two miRNA sponges can inhibit cancer cell growth significantly. Abstract : A method to establish desired lung cancer teargeted miRNA sponge with accurate copy number of sponge sequence.